ANALISIS KUALITAS BUTIR SOAL PADA UJI COBA EVALUASI PEMBELAJARAN MATEMATIKA - SURBAKTI, ICCA WIDYA (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
Education is one of the important components in life. One of the components of education that has an important role in supporting the educational process is evaluation. This study aims to analyze the quality of learning evaluation questions in mathematics subjects through instrument trials with a total of 30 subjects of Senior High School (SMA) students who were taken randomly. The research method used is quantitative descriptive which aims to analyze the quality of the learning evaluation test questions. The analysis involves several aspects, namely reliability, discriminatory power, level of difficulty, and validity of the test items. The data was obtained from the participants' answer scores on five questions with a score weighting of 20 for correct answers and 0 for incorrect answers. The results of the reliability test show a coefficient value of 0.79 indicating that this test has a high level of consistency, so it can be relied on in learning evaluation. Based on the summary of the analysis results, two questions are recommended for use, while the other three questions need to be revised to improve the quality of the evaluation instrument. This study emphasizes the importance of item analysis to ensure that evaluation instruments have adequate validity, reliability, discriminatory power, and level of difficulty. ABSTRAKPendidikan merupakan salah satu komponen penting dalam kehidupan. Salah satu komponen pendidikan yang memiliki peran penting untuk mendukung proses pendidikan yaitu evaluasi. Penelitian ini bertujuan untuk menganalisis kualitas butir soal evaluasi pembelajaran pada mata pelajaran matematika melalui uji coba instrumen dengan jumlah subjek sebanyak 30 orang siswa Sekolah Menengah Atas (SMA) yang diambil secara acak. Metode penelitian yang digunakan kuantitatif deskriptif yang bertujuan untuk menganalisis kualitas butir soal tes evaluasi pembelajaran. Analisis melibatkan beberapa aspek, yaitu reliabilitas, daya pembeda, tingkat kesukaran, dan validitas butir soal. Data diperoleh dari skor jawaban peserta pada lima butir soal dengan bobot skor jawaban benar sebesar 20 dan salah sebesar 0. Dari hasil uji realibilitas menunjukkan nilai koefisien sebesar 0.79 mengindikasikan bahwa tes ini memiliki tingkat konsistensi yang tinggi, sehingga dapat diandalkan dalam evaluasi pembelajaran. Berdasarkan rangkuman hasil analisis, dua butir soal direkomendasikan untuk digunakan, sementara tiga butir lainnya perlu direvisi untuk meningkatkan kualitas instrumen evaluasi. Penelitian ini menegaskan pentingnya analisis butir soal guna memastikan instrumen evaluasi memiliki validitas, reliabilitas, daya pembeda, dan tingkat kesukaran yang memadai.